The NICU during COVID-19 Pandemic: Impact on Maternal Pediatric Medical Traumatic Stress (PMTS) - Raho, Laura; Bucci, Silvia; Bevilacqua, Francesca; Grimaldi, Teresa; Dotta, Andrea; Bagolan, Pietro; Aite, Lucia (American Journal of Perinatology, 2022)
Objective The objective of this paper was to assess how hospital and outpatient clinic policies changes due to the coronavirus disease 2019 (COVID-19) pandemic impact pediatric medical traumatic stress (PMTS) symptoms in mothers of newborns admitted in a neonatal intensive care unit (NICU).Study Design Observational case-control study included the comparison between mothers of infants admitted in the NICU at birth during the COVID-19 pandemic and mothers of infants admitted in the NICU before the COVID-19 pandemic. The control group was selected matching 1:1 with the study group for the following infants' clinical variables: gender, type of pathology, gestational age, weight at birth, day of recovery, ventilator time days, and associated malformations. The Italian version of the Impact of Event Scale—Revised (IES-R) was used as a measure of PMTS.Result Mothers of the study group (50) scored significantly higher than mothers of the control group on three of four scales of IES-R (“IES-R total”: F = 6.70; p = 0.011; IES-R subscale “intrusion”: F = 7.45; p = 0.008; IES-R subscale “avoidance”: F = 8.15; p = 0.005). A significantly higher number of mothers in the study group scored above the IES-R total clinical cut-off compared with mothers of control group (72 vs. 48%; Chi2 = 6.00; p = 0.012).Conclusion The COVID-19 pandemic acted as superimposed stress in mothers of newborns admitted in the NICU at birth determining high levels of PMTS. Clinicians and researchers should identify and implement novel strategies to provide family-centered care during the COVID-19 pandemic and beyond.Key Points
Keywords: pediatric medical traumatic stress; NICU; COVID-19; maternal psychological distress